Transforming English Language Learning in Elementary Schools Through Augmented Reality - Purnama, Yulian; Wijayanto, Pikir Wisnu; Barlian, Yelly Andriani; Nurbani, Sri; Syathroh, Isry Laila (Universitas Pendidikan Ganesha, 2024)
The problem with learning English in elementary schools is the low learning outcomes of students, especially in understanding the material. The urgency of applying Augmented Reality (AR) technology as a learning medium is to improve students' understanding of English more interestingly and interactively. This research aims to evaluate the effectiveness of using AR in improving student learning outcomes in English subjects in elementary schools. The research method used is quantitative with the research subjects being elementary school students. The data collection technique is carried out through questionnaires filled out by students after using AR-based learning media. The data analysis technique used is a statistical analysis to measure the increase in student learning outcomes before and after using AR. The research results show that there is a significant increase in students' understanding of English material after using AR as a learning medium. This research concludes that the application of AR is effective in improving student learning outcomes in English subjects in elementary schools. The implication of this research is the need to integrate AR technology into the English language learning curriculum in elementary schools to improve the quality of learning and students' understanding of the subject matter.